2000
DOI: 10.1016/s0735-1097(99)00632-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor in patients with acute myocardial infarction

Abstract: The extent of myocardial damage contributes to the elevation of serum VEGF levels in AMI. VEGF produced by PBMCs may play an important role in the improvement of left ventricular function by promoting angiogenesis and reendothelialization after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
2
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 27 publications
2
96
2
9
Order By: Relevance
“…In vitro experimental studies have shown that VEGF, Ang-2, and Tie-2 but not Ang-1 expression is upregulated in ischemic myocardium, 3,5 whereas clinical studies in patients with ACS (AMI patients) have shown increased peripheral blood VEGF. [7][8][9][10][11] The present study shows that in addition to raised VEGF and Tie-2 levels, Ang-2 levels were also raised in ACS patients within 24 hours of presentation, although Ang-1 levels were not different compared with those of healthy control subjects and SA patients. Patients with evidence of myocardial damage (ie, AMI) had the highest levels of Ang-2, VEGF, and Tie-2 compared with other groups.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In vitro experimental studies have shown that VEGF, Ang-2, and Tie-2 but not Ang-1 expression is upregulated in ischemic myocardium, 3,5 whereas clinical studies in patients with ACS (AMI patients) have shown increased peripheral blood VEGF. [7][8][9][10][11] The present study shows that in addition to raised VEGF and Tie-2 levels, Ang-2 levels were also raised in ACS patients within 24 hours of presentation, although Ang-1 levels were not different compared with those of healthy control subjects and SA patients. Patients with evidence of myocardial damage (ie, AMI) had the highest levels of Ang-2, VEGF, and Tie-2 compared with other groups.…”
Section: Discussionmentioning
confidence: 43%
“…11 Two studies have shown significant correlations between VEGF and peak CK levels, 7,9 suggesting that the extent of myocardial damage may be linked to elevated circulating VEGF levels. We confirm this aspect in the present study, adding the novel finding that Tie-2 and Ang-2 are also significantly correlated with peak total CK levels in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…MNCs and ECs have been shown to produce and release VEGF, a potent angiogenic cytokine (Hojo et al, 2000;Namiki et al, 1995). In the present study, A, Exogenous addition of rhVEGF (10 ng/mL) significantly enhanced the differentiation of PB-MNCs into EPC-like AT cells.…”
Section: Discussionmentioning
confidence: 52%
“…Human MNCs produce and secrete VEGF protein (Hojo et al, 2000), which could modulate the differentiation of PB-MNCs into EPCs through an autocrine mechanism (Risau, 1995). We examined the role of VEGF released from PB-MNCs on the differentiation of PB-MNCs into EPCs.…”
Section: Role Of Autocrine Vegf In Epc Differentiationmentioning
confidence: 99%
“…VEGFhas been shown to be an important factor in the pathogenesis of vascularrelated diseases, including the growth of tumors, vascular dysfunction in diabetes mellitus, and atherosclerosis of the coronary arteries (13,27,28). The increased VEGFproduction found in OSASpatients might contribute to new vessel formation in ischemic and atherosclerotic vascular regions.…”
Section: Discussionmentioning
confidence: 99%